Pengaruh TATO, DER, CR, dan NPM Terhadap Perubahan Laba Pada Perusahaan Sub Sektor Batu Bara Yang Terdaftar di Bei Tahun 2020 - 2023 - Azizeh, Fahrothul; Nadhiroh, Umi; Wahyu Arida, Ririn (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to explain and also prove the hypothesis regarding the effect of total asset turnover (TATO), debt to equity ratio (DER), current ratio (CR), and net profit margin (NPM) on profit changes in coal sub-sector companies listed on the Indonesia Stock Exchange in 2020-2021. The study uses quantitative research using purposive sampling techniques, the population is coal sub-sector companies and a sample of 32 financial reports from 8 companies in 2020-2023. The analytical techniques used are descriptive analysis, panel data estimation methods, classical assumption tests, t-tests (partial), F-tests (simultaneous), and coefficients of determination (R2). The results of the research that has been conducted, it can be concluded that total asset turnover partially does not have a significant effect on profit changes. The debt to equity ratio variable partially has a positive and significant effect on profit changes. The current ratio variable partially has a positive and significant effect on profit changes. The net profit margin variable partially has no effect on profit changes with. Simultaneously, the variables total asset turnover, debt to equity ratio, current ratio, and net profit margin influence changes in profit.